The care needs of persons with oropharyngeal dysphagia and their informal caregivers: A scoping review. - Aurora Ninfa; Valeria Crispiatico; Nicole Pizzorni; Marta Bassi; Giovanni Casazza; Antonio Schindler; Antonella Delle Fave (PLoS ONE)
Introduction Besides affecting physical health, Oropharyngeal Dysphagia (OD) entails limitations in daily activities and social participation for both patients and their informal caregivers. The identification of OD-related needs is crucial for designing appropriate person-centered interventions. Aims To explore and map the literature investigating the care needs related to OD management of adult persons with OD and their informal caregivers during the last 20 years. Methods A scoping review was conducted and reported following PRISMA guidelines. Five electronic databases and reference lists of eligible publications were searched for original works in English or Italian, published between January 2000 and February 2021. Two independent raters assessed studies' eligibility and extracted data; a third rater resolved disagreements. Extracted care needs were analyzed using a Best fit framework synthesis approach. Results Out of 2,534 records preliminarily identified, 15 studies were included in the review and 266 care needs were extracted. All studies were conducted in Western countries. Research methods primarily consisted of qualitative interviews and focus groups (14 studies, 93.3%); head and neck cancer was the most frequent cause of patients' dysphagia (8 studies, 53.3%); caregivers' perspective was seldom investigated (5 studies, 33.3%). Both patients and caregivers primarily reported social (N = 77; 28.9%) and practical (N = 67; 25.2%) needs, followed by informational (N = 55; 20.7%) and psychological (N = 54; 20.3%) ones. Only patients reported physical needs (N = 13; 4.9%), while spiritual needs were not cited. Conclusions The recurrence of personal and social needs besides physical ones highlighted the manifold impact of OD on patients' and caregivers' lives. Larger and more focused studies are required in order to design tools and interventions tailored to patients' and caregivers' needs.